Outcomes of high-grade gastrointestinal graft-versus-host disease posthematopoietic stem cell transplantation in children - Uygun, Vedat; Kocacık Uygun, Dilara Fatma; Daloğlu, Hayriye; Irmak Öztürkmen, Seda; Karasu, Gülsün; Hazar, Volkan; Yeşilipek, Akif (Lippincott Williams & Wilkins, 2016)
We explored the clinical course of acute high-grade gastrointestinal graft-versus-host disease in children in a single center. This was a retrospective analysis of 28 pediatric patients who presented with a clinical diagnosis of stage III and IV acute graft-versus-host disease (aGVHD) of the gastrointestinal system (GIS). Generally, skin involvement was the initial manifestation of aGVHD that began in the first 3 weeks of hematopoietic stem cell transplantation (HSCT); on the other hand, GIS involvement predominated after the second week of HSCT. Reported adult data show a survival rate of only 25%; however, our study showed more favorable outcomes in children with a survival rate of 55%. We monitored levels of albumin and immunoglobulin G and observed low levels overall during treatment of unresponsive patients, although only albumin levels were shown to be significantly different. We observed a significant increase in mortality with the use of antithymocyte globulin in GIS aGVHD, although antithymocyte globulin used for graft-versus-host disease prophylaxis had no demonstrable effect on GIS aGVHD mortality. Whether the significantly lower GIS aGVHD mortality among the children recruited in our study than among their historical adult counterparts is a primary result of the specific attributes of the pediatric GIS, or whether it originated from HSCT kinetics remains to be determined by future studies.
WOS: 000388566200044
PubMed ID: 27858879
Keywords: Children; Gastrointestinal Graft-Versus-Host Disease; Hematopoietic Stem Cell Transplantation